A multiplex and fast detection platform for microRNAs based on a self-priming microfluidic chip and duplex-specific nuclease. Issue 2 (17th November 2020) - Zou, Zheyu; Liu, Yuanhui; Xia, Liping; Hu, Zhenming; Yin, Juxin; Mu, Ying
Abstract : A self-priming microfluidic chip for multiplex and fast detection of microRNAs was developed. Abstract : MicroRNA expression levels highly correlate with the occurrence, diagnosis and prognosis of disease. However, challenges remain in establishing a multiplex and fast detection method. Here, we developed a multiplex and fast detection platform for microRNAs based on a self-priming microfluidic chip and duplex-specific nuclease. It can detect three types of miRNAs, including miR-100, miR-155, and Let-7a, simultaneously at 50 °C within 1 h. The probes are pre-introduced into the chip using the self-priming method and cross-contamination can be avoided by using a screw valve. The reagent consumption and cost have been largely reduced in this work compared to the traditional detection method. This chip also exhibits good quantitative performance and specificity. As a proof of concept, we detect three types of microRNAs from different cancer cell lines, which demonstrates its potential in real sample analysis. In summary, this microfluidic chip shows great advantages in multiplex, fast and simple detection of microRNAs, and possesses great potential in the early diagnosis of miRNA-related diseases, especially for point-of-care application.